Financial accountability of Waqf (Pious endowment) institutions: the case of budgeting practices in state Islamic religious councils in Malaysia - Siraj, Siti Alawiah; Karbhari, Yusof (2014)
Islamic Waqf Organisations are unique to the Islamic World. However, over the last two decades Islamic Waqf (i.e., Islamic endowment) institutions in Malaysia have been under intense pressure to improve their financial accountability and budgetary practices. Thus, this study empirically examines the extent of financial accountability of waqf management in State Islamic Religious Councils (SIRCs) by examining, in particular, their budgeting practices. Data was collected by means of semi-structured interviews with senior finance officers of the twelve SIRCs and the two baytulmal (House of wealth) institutions in existence in Malaysia. The study finds that that the participative budgeting and bottom-up budget preparation are the prevalent budgeting culture; (2) budget allocation were thoroughly deliberated via technical examinations and Shari’ah screening before being approved by higher level authorities for spending ; (3) budgetary controls strictly emphasized on budget compliance due to financial constraints and less focus on the effectiveness of budget consumption; and (4) the existence of inherent challenges of shortages in financial and human resource and a clear lack of expertise and top management commitment along with weak management information systems which inevitably act as major hindrance to achieving an effective financial accountability system.